1999
DOI: 10.1093/gerona/54.12.b539
|View full text |Cite
|
Sign up to set email alerts
|

Age-Associated Impairment in Brain MAPK Signal Pathways and the Effect of Caloric Restriction in Fischer 344 Rats

Abstract: Mitogen-activated protein kinases (MAPKs) play important roles in cell proliferation, differentiation, and apoptosis. Important functional roles for MAPKs in postmitotic cells have recently been suggested. In the present study, we investigated the effect of aging on the brain ERK (extracellular signal-regulated kinase) and p38 MAPK signaling pathways of Fischer 344 rats. The results show that basal tyrosine-phosphorylated ERK1/ERK2 in cortex of 24-month-old rats was reduced by 36%-59%, compared to 6- and 12-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 27 publications
1
44
0
1
Order By: Relevance
“…This potentially linked together aging, VSMC proliferation and atherosclerosis (Rivard et al, 2000;Gennaro et al, 2003). These findings in VSMC are in contrast to reports of an age-related decrease in ERK1/2 activation in several different tissues or cells, such as the brain (Zhen et al, 1999), hepatocytes (Hutter et al, 2000), or systems of in vitro senescence (Lorenzini et al, 2002). This discrepancy likely represents tissue and cell specificity and differences in the proliferative capacity of cells.…”
Section: Discussionmentioning
confidence: 78%
“…This potentially linked together aging, VSMC proliferation and atherosclerosis (Rivard et al, 2000;Gennaro et al, 2003). These findings in VSMC are in contrast to reports of an age-related decrease in ERK1/2 activation in several different tissues or cells, such as the brain (Zhen et al, 1999), hepatocytes (Hutter et al, 2000), or systems of in vitro senescence (Lorenzini et al, 2002). This discrepancy likely represents tissue and cell specificity and differences in the proliferative capacity of cells.…”
Section: Discussionmentioning
confidence: 78%
“…In a recent report, it was shown that BDNF mRNA expression in the CA1 of aged rats that performed well in a spatial learning task was enhanced after training, but this increase was not observed in rats which exhibited an impairment in spatial learning and, in addition, basal expression of BDNF mRNA was lower in this group (546). Interestingly, age-related decreases in TrkB expression (116, 544), TrkB phosphorylation (Gooney et al, unpublished data), and ERK activation (235,397,660) have been reported, whereas ERK phosphorylation was decreased in dentate gyrus of aged rats that did not sustain LTP (397).…”
Section: Neurotrophins Long-term Potentiation and Memorymentioning
confidence: 98%
“…It is unclear whether or not these discrepancies are due to tissue specificity of p38 and ERK responses to the aging process. Nevertheless, the activation of ERK in response to epithelial growth factor is decreased in cortical brain slices and hepatocytes from old rats (148,259), indicating reduced sensitivity to stimuli in these tissues during aging.…”
Section: Mitochondrial Regulation Of Cytosolic Signalingmentioning
confidence: 99%